2010
DOI: 10.1192/bjp.bp.109.067942
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing dementia in people with diabetes and mild cognitive impairment

Abstract: Diabetes mellitus increases not only the risks of dementia and mild cognitive impairment but also the risk of progression from such impairment to dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 27 publications
6
78
0
Order By: Relevance
“…How diabetes mellitus affects Aβ catabo lism and AD risk is not yet well understood. Patients with diabetes mellitus are estimated to be 1.4-2.0-fold more likely than healthy individuals to develop AD 72,73 , although these claims need to be verified in patients with biomarker-confirmed AD. In patients with diabetes mellitus, insulin resistance substantially compromises the positive effects of insulin on both cognition and hepatic clearance of circulating Aβ 74,75 , resulting in AD-like alterations in the brain.…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…How diabetes mellitus affects Aβ catabo lism and AD risk is not yet well understood. Patients with diabetes mellitus are estimated to be 1.4-2.0-fold more likely than healthy individuals to develop AD 72,73 , although these claims need to be verified in patients with biomarker-confirmed AD. In patients with diabetes mellitus, insulin resistance substantially compromises the positive effects of insulin on both cognition and hepatic clearance of circulating Aβ 74,75 , resulting in AD-like alterations in the brain.…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…Although not all research results are in agreement, the majority of the data suggests that diabetics, specifically T2D subjects, are at much higher risk of developing AD than normal subjects. Elderly people with diabetes have an especially increased risk of mild cognitive impairment (MCI) [18] and an association of diabetes with MCI varies with amyloid subtype (amnestic) MCI and nonamnestic MCI) and number of domains, and with the sex of the patient, with females being more susceptible than males [19]. Diabetes as a significant risk factor for dementia or AD has been clearly established by studies in the US [20] and several other countries (Taiwan [21], China [22], Japan [23], and Finland [24]).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Numerous studies have documented a strong association between diabetes and Alzheimer's Disease (AD) [16], [17], [18], [19], [20], [44]. However, the mechanisms underlying this association have not been clearly established.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Besides the well-known connection between T2DM and peripheral nervous system disease, the diabetes-induced lesions in the central nervous system (CNS), such as cerebrovascular disease and cognitive dysfunction, are receiving increased attention. Several epidemiological studies have found that T2DM is an independent risk factor for both Alzheimer's disease (AD) and vascular dementia (VaD) [1,2]. In addition, further research has shown that T2DM may also exercise influence on the prevalence of mild cognitive impairment (MCI), which is considered a pre-clinical stage of dementia.…”
Section: Introductionmentioning
confidence: 99%